Temporal Behavior of Tree Communities in Different Soil Classes - Santos,Alisson Borges Miranda (2019)
ABSTRACT The objective of this work was to evaluate if the soil heterogeneity expressed by the different soil classes would condition tree communities with different dynamic behaviors. The data were collected from 25 plots sized 20 × 20 (400 m²), 10 of them with Inceptisols, 9 with Ultisols, 5 with Entisols B and 1 with Entisols A. All individuals with DBH ≥ 5.0 cm in the plots were sampled in 2000, 2005, 2009 and 2015. Rates of mortality, recruitment, gain, loss and turnover dynamics in number of individuals and basal area were estimated for each soil class. The tree communities present in the soil classes showed no differences in the dynamic behavior to the point of expressing edaphic fragment heterogeneity. The differences are associated with stochastic fluctuations in rates caused by small disturbances, suggesting little influence of the soils on the dynamics of small-scale communities.